Potencial genético de linhagens elite de feijoeiro-comum para fixação biológica de nitrogênio - Dias, Polianna Alves Silva (2017)
In species rich in protein, like common bean, the nitrogen is considered as the most limiting nutrient in the development of the crop. One way to acquire the N by common bean is through biological nitrogen fixation (BNF). Despite its importance, there are no studies aiming the selection of common bean genotypes under rhizobia inoculation in multiple environments. Thus, the objectives of this studies were: to study the effect of interaction (GxF) of common bean elite lines with nitrogen fertilization and/or rhizobia inoculation; to select lines with high grain yield adaptability and stability and high agronomic performance when inoculated with rhizobia; to assess the variability of the elite lines for the nodulation traits; and to identify lines with superior nodulation traits under BNF cultivation. They were evaluated 19 carioca genotypes and 15 of the black group, in trials conducted separately by grain group. At first, experiments for the evaluation of agronomic traits were conducted at the states of Goiás, Paraná, Mato Grosso and at Distrito Federal, in three sowing seasons (rainy, winter and dry), in 2011 and 2012. Two trials were installed at each environment (location/sowing season/year), one with mineral nitrogen fertilization (80 kg N ha-1) and another with the inoculation of the seeds with Rhizobium tropici and R. freirei strains. The grain yield, sieve yield, 100 grains weight, plant architecture, lodging tolerance and the reaction to anthracnose and angular leaf spot were evaluated. Then, the lines were evaluated during rainy/2013 and winter/2014 seasons, at Santo Antônio de Goiás/GO, under rhizobia inoculation and nitrogen fertilization, in which they were assessed the nodule number, nodule dry and specific weight, nodules activity and shoot dry weight. The relative nodulation index was used on the selection of lines for the nodulation traits. Individual and combined analyses of variance were performed and they were estimated the Spearman correlations and the coincidence index on the selection of the best 30% lines with inoculation and with N fertilization. Grain yield adaptability and stability analyses were performed by the Nunes graphical method. Even though the interaction GxF was significant for some traits in both grain groups, it did not influence on the selection of the best genotypes. The lines of both groups are more productive when fertilized with mineral N, however, the carioca lines lodge less under BNF. The carioca line CNFC 15086 and the cultivars of black group BRS FP403 and BRS Esteio are indicated for cultivation under both N sources. The lines of both grain groups show higher performance for nodulation traits when inoculated. The genotypes BRS Sublime, CNFC 15010 and CNFC 15003 of the carioca group, and BRS Campeiro and CNFP 15177 of the black group are selected for the nodulation traits.